Measuring bone healing in fractures and fusions. Issue 4 (August 2022) - Voller, Thomas; Ahmed, Maryam; Ho, Sebastian; Kozhikunnath, Arun; Bendall, Stephen
Abstract: Measuring bone healing in fracture and fusions is a subjective assessment based on both clinical examination and radiological interpretation. There is not universal agreement over what a non-union is exactly, although in general practice a temporal limit is applied to healing fractures and osteotomies. There is uncertainty around how much healing is required for a satisfactory clinical outcome. This article aims to briefly recap on the process of bone healing and then examine the methods used to answer the question as to whether a fracture or fusion has united or not. These will include clinical judgements, radiological assessments, serological tests, mechanical techniques and the use of patient-reported outcome measures. The reality is clinical judgement remains key aided by selected investigations as outlined above.